2020
DOI: 10.3390/brainsci10030174
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Coordination, Visual Perception and Head Stability during Running

Abstract: Perception and action are coupled such that information from the perceptual system is related to the dynamics of action in order to regulate behavior adaptively. Using running as a model of a cyclic behavior, this coupling involves a continuous, cyclic relationship between the runner's perception of the environment and the necessary adjustments of the body that ultimately result in a stable pattern of behavior. The purpose of this paper is to illustrate how individuals relate visual perception to rhythmic loco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Perception plays a critical role in shaping the coordination, stability, and organization of motor actions (19; 20; 21; 22; 23; 24; 25; 26; 27; 28; 29; 30). Perception fundamentally contextualizes and attributes meaning to sensations to produce meaningful actions.…”
Section: Mainmentioning
confidence: 99%
“…Perception plays a critical role in shaping the coordination, stability, and organization of motor actions (19; 20; 21; 22; 23; 24; 25; 26; 27; 28; 29; 30). Perception fundamentally contextualizes and attributes meaning to sensations to produce meaningful actions.…”
Section: Mainmentioning
confidence: 99%
“…It comes as no surprise, then, that eye and body movements tend to be coupled: Not only do the eyes interact with how the body and the head move (Guitton, 1992;Hamill, Lim, & Emmerik, 2020;Imai, Moore, Raphan, & Cohen, 2001;Moore et al, 2001;Solman, Foulsham, & Kingstone, 2017), they have also been shown to move in coordinated fashion with the feet in a stepping task (Hollands & Marple-Horvat, 2001). In walking more generally, higher terrain difficulty correlates with a lowered gaze ('t Hart & Einhäuser, 2012), a relationship that holds not just with respect to terrain difficulty, but also to the walker's assessment of the terrain (Thomas, Gardiner, Crompton, & Lawson, 2020).…”
Section: The Perception and Action Of Walkingmentioning
confidence: 99%
“…Visual acuity during simulated running is also lower than standing still (Demer & Viirre, 1996), and the vestibulo‐ocular reflex is only able to counteract ~75% of the head's rotational velocity with eye rotation in this paradigm (Grossman et al, 1989). The experimental challenge of gaze stability has also been shown to cause changes in lower limb and trunk kinematics, altering running mechanics in order to maintain stable gaze within the prescribed range (Hamill et al, 2020; Lim et al, 2017). It is hypothesized that the nuchal ligament, along with active muscle contraction, resists pitching torques caused by collisions with the ground and therefore aids in the maintenance of gaze stability (Gellman & Bertram, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When subjects were asked to fix their gaze within a narrow window during running they reduced both hip and ankle motion while increasing knee flexion, adopting a more compliant gait that attenuated the collision impulse as it traveled up the body from the foot to the head (Lim et al, 2017). Further attenuation of the collision impulse can occur through modulating trunk motions, which oscillate once per step (Hamill et al, 2020; Thorstensson et al, 1984), and appear to aid in head balance in the frontal plane compared with chimpanzee bipedal gait (Thompson et al, 2018). Therefore, head stabilization can be considered an integrated system involving the entire body, with superior trapezius activity being one component of the system.…”
Section: Introductionmentioning
confidence: 99%